Media and Political Participation in North Africa - Mathilde Maurel; Charlemagne Nikiema (Fondation pour les études et recherches sur le développement international (FERDI), 2016)
We examine the role of new decentralized media (the internet) vs old media (television) on individuals' political engagement in North Africa. Drawing our data from the Afrobarometer round 5 survey, we tackle issues of endogeneity by resorting first to a propensity score matching method to identify the effect of media on political participation. We then address endogeneity by relying to a bivariate probit model while using lightening activity as an instrument for media. The analysis evidences the political power of the internet and TV. Getting news from internet reduces voting but increases protests, while TV watching induces more vote and less protest. This effect is channeled through the impact of media on the perception about political institutions, which differs across the different media.
Keywords: D74; F50; O55; L96; 330; media; political participation; North Africa